A systematic review on methods used to evaluate patient preferences in psoriasis treatments. (19th July 2016) - Gutknecht, M.; Schaarschmidt, M.‐L.; Herrlein, O.; Augustin, M.
Abstract: In the treatment of psoriasis and psoriatic arthritis, recently approved medications undergo the 'early benefit assessment' in Germany. Psoriasis treatments differ in a multiplicity of characteristics like side‐effects, beneficial effect, cost and process attributes, which serve to evaluate the patient‐relevant benefit compared to standard treatments. Patient preferences might help to aggregate the various patient‐relevant outcomes into a single measure. In this context, besides the calculation of the quality‐adjusted life‐years (QALYs), the Institute for Quality and Efficiency in Health Care (IQWiG) refers to methods of multi‐criteria decision making or preference evaluation like analytic hierarchy process and conjoint analysis. The objective was to give an overview of methods that have been used in international published studies to evaluate patient preferences in psoriasis treatments. The review is based on a systematic literature research on December 2014 in selected electronic databases, using the keywords 'psoriasis' and 'preferences' as well as the name of specific methods, known from the literature to evaluate patient preferences. The search resulted 389 hits without duplicates. 21 articles met the inclusion criteria. Depending on the study objective, preferences were elicited for health states, health state domains, treatment attributes or treatment alternatives focusing on different outcomes of preferences. Thereby, different methods were used in included studies. For this reason, there is no single outcome available that might be useful in the benefit assessment of the IQWiG. Willingness‐to‐pay, often included as part of a conjoint analysis, was the predominant method to elicit preferences. So far, the analytic hierarchy process has not been used in psoriasis studies. The use of this method in future studies might provide new essential knowledge in the evaluation of patient preferences in psoriasis treatments. However, a clear assignment when to use which method is not given by the IQWiG and should be prioritized.